Islamic Boarding School Educational Values in Efforts to Realize Student Life Skills at University of Darussalam Gontor - Rochmat, Cecep Sobar; Yoranita, Angelica Silfana Prisca; Putri, Haqiyah Afifi (Qualitative and Quantitative Research Center, 2022)
The fading of character values causes problems such as fights, brawls, and violence. Through the reform of educational programs, it can realize morals for the future sustainability of the younger generation. Life skills shape humans into quality humans and direct the goals of human life. The purpose of this research is to describe the Islamic educational values and the life skills of students at the University. This research is field research and uses a qualitative descriptive approach. The research location is on the female campus of University of Darussalam Gontor, with research subjects being Kyai, Ustadz, Ustadzah, administrators, and students. Primary data is sourced from interviews, and secondary data is sourced from relevant books, articles, and documents. Based on data analysis research and interviews, it can be concluded that the foundation of the philosophy at University of Darussalam Gontor is guided by the Al-Qur'an and Sunnah, the soul/philosophy of life. The fostering of student life skills creates University of Darussalam Gontor graduates who can fight for their totality selflessly and firmly to their Islam beliefs. They are implementing campus activities by optimizing the 24-hour educational process based on discipline in the Islamic boarding school curriculum.